Mapping the research landscape of nature-based solutions in urbanism - Li, Lei; Cheshmehzangi, Ali; Chan, Faith Ka Shun; Ives, Christopher D. (2021)
Nature-based solutions (NBS) are an innovative concept that mimics the processes of natural ecosystems, popularized principally in the European Union. With a substantial body of literature amassed since the term’s inception in 2015, there is a need to systematically review existing literature to identify overarching gaps and trends, according to disciplinary focus, geographic scope, and key themes, and direct future research inquiry and policy recommendations. This review consists of bibliometric analysis and thematic analysis for NBS studies in urbanism. NBS studies were found to relate strongly with other concepts of ‘Ecosystem Services’, ‘Green Infrastructure’, ‘Climate Change’, and ‘Risk management and Resilience’, which align with four major thematic goals set by the European Commission. Within NBS scholarship, various sub-themes have emerged, namely, ‘Greening’, ‘Urban Development’, ‘Water’, ‘Wellbeing’, and ‘Governance’. Furthermore, we illustrate that the amount and thematic focus of NBS research have been unevenly distributed worldwide. Analysis of emerging trends shows a recent increase in topics, such as adaptive governance of NBS, and the incorporation of social justice in sustainability transitions. Based on an assessment of extant NBS literature, we offer some recommendations for the future direction of the research fields.